Evaluation of a novel Surgicric® cricothyroidotomy device for emergency tracheal access in a porcine model. (17th November 2015) - King, W.; Teare, J.; Vandrevala, T.; Cartwright, S.; Mohammed, K. B.; Patel, B.
Summary: A can't intubate, can't ventilate scenario can result in morbidity and death. Although a rare occurrence (1:50 000 general anaesthetics), it is crucial that anaesthetists maintain the skills necessary to perform cricothyroidotomy, and are well‐equipped with appropriate tools. We undertook a bench study comparing a new device, Surgicric ®, with two established techniques; the Melker Emergency Cricothyroidotomy, and a surgical technique. Twenty‐five anaesthetists performed simulated emergency cricothyroidotomy on a porcine model, with the primary outcome measure being insertion time. Secondary outcomes included success rate, tracheal trauma and ease of use. The surgical technique was fastest. The median (IQR [range]) was 81 (62–126 [37–300]) s, followed by the Melker 124 (100–217 [71–300]) s, and the Surgicric 127 (68–171 [43–300]), p = 0.003. The Surgicric device was the most traumatic, as evaluated by a blinded Ear, Nose and Throat surgeon. Subsequently, the authors contacted the device manufacturer, who has now modified the kit in the hope that its clinical application might be improved. Further studies are required to evaluate the revised model.